1998
DOI: 10.1161/01.res.82.4.464
|View full text |Cite
|
Sign up to set email alerts
|

Normal Development of the Outflow Tract in the Rat

Abstract: The outflow tract (OFT) provides the structural components forming the ventriculoarterial connection. The prevailing concept that this junction "rotates" to acquire its definitive topography also requires a concept of "counterrotation" and is difficult to reconcile with cell-marking studies. Rats between 10 embryonic days (EDs) and 2 postnatal days were stained immunohistochemically and by in situ hybridization. DNA replication was determined by incorporation of bromodeoxyuridine and apoptosis by the annexin V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
154
0
4

Year Published

1999
1999
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(166 citation statements)
references
References 47 publications
8
154
0
4
Order By: Relevance
“…Indeed, the proximal conus absorption pulling down the distal conus and the truncus, as indicated by several authors (Goor et al, 1972;Pexieder, 1975;Watanabe et al, 2001), might produce, we think, some sort of sliding of the myocardial cuff down along the cardiac jelly, thereby allowing the aortic sac to envelop the intercalated truncal swellings and ultimately the developing sinuses of Valsalva. In this respect, it is also important to emphasize, as previously mentioned, that since no apoptosis was identified along the truncal myocardial wall (Ya et al, 1998a), as a consequence, the myocardial retraction is not to be referred to as a programmed cell death. Specifically, as far as the development of the sinuses of Valsalva is concerned, Anderson et al (2003) emphasize the fact that some sort of cavitation is supposed to occur within the truncal and the intercalated endocardial cushions.…”
Section: Truncal Septation: Development Of the Arterial Valvesmentioning
confidence: 94%
See 2 more Smart Citations
“…Indeed, the proximal conus absorption pulling down the distal conus and the truncus, as indicated by several authors (Goor et al, 1972;Pexieder, 1975;Watanabe et al, 2001), might produce, we think, some sort of sliding of the myocardial cuff down along the cardiac jelly, thereby allowing the aortic sac to envelop the intercalated truncal swellings and ultimately the developing sinuses of Valsalva. In this respect, it is also important to emphasize, as previously mentioned, that since no apoptosis was identified along the truncal myocardial wall (Ya et al, 1998a), as a consequence, the myocardial retraction is not to be referred to as a programmed cell death. Specifically, as far as the development of the sinuses of Valsalva is concerned, Anderson et al (2003) emphasize the fact that some sort of cavitation is supposed to occur within the truncal and the intercalated endocardial cushions.…”
Section: Truncal Septation: Development Of the Arterial Valvesmentioning
confidence: 94%
“…Furthermore, Ya et al (1998a) emphasize the fact that no apoptosis was found at the truncal level; consequently, they excluded the fact that the truncal cardiomyocytes were replaced by a local invasion of mesodermic mesenchymal cells differentiating subsequently into smooth muscle cells. In contrast, Waldo et al (2005b) show that SHF pharyngeal mesoderm provides smooth muscle precursor cells to the caudal portion of the aortic sac.…”
Section: Truncal Septation: Development Of the Arterial Valvesmentioning
confidence: 97%
See 1 more Smart Citation
“…Several processes have been proposed to account for the apparent shortening of the cardiac outlet: retraction of the distal myocardial rim toward the ventricle, perhaps including absorption of conal myocardium predominantly into the right ventricle (Anderson et al, 1974;Thompson and Fitzharris, 1979;Thompson et al, 1987); the loss of myocardium through apoptosis, prominent along the conal (proximal) myocardium (Watanabe et al, 1998;van den Hoff et al, 2000;Watanabe et al, 2001;Cheng et al, 2002;Kubalak et al, 2002;Sugishita et al, 2004), myocardialization of the proximal cushions (van den Hoff et al, 1999) and nonapoptotic loss of myocardium from the distal end (truncus) of the outlet through reorganization as arterial muscle (Arguello et al, 1978;Ya et al, 1998b;Yang et al, 2004). However, the underlying mechanisms for the replacement of the myocardial wall with smooth muscle are largely unknown and a topic of controversy.…”
Section: Introductionmentioning
confidence: 99%
“…The endocardium undergoes EMT at the onset of endocardial cushion formation, when the endocardial cells invade the cardiac jelly, which is followed by migration of the NCC into the conotruncal ridges. Proliferation of the mesenchymal cells and cell apoptosis precede compaction and fusion of the ridges before myocardialization (35,41). While the essential role of NCC in the distal septation of the OFT is very well established, their participation in septation of the proximal OFT is still controversial even though the use of transgenic mice expressing markers in NCC has shown their presence in endocardial ridges (18,38).…”
Section: Vol 26 2006 Trap␣ In Mouse Heart Morphogenesis 7767mentioning
confidence: 99%